ANALYSIS ON THE LEVEL OF PHYSICAL WORKLOAD OF COAL HANDLING CONTROL ROOM AND SHIP UNLOADER OPERATION IN CILACAP STEAM TURBINE POWER PLANT - Wahyu Ismail Kurnia; Muhammad Isradi Zainal; Alex Kisanjani (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2021)
The company mentions the frequent inaccuracies between coal unloading data on barges with coal availability in coal silos and stockpiles carried out by Coal handling Control Room (CHCR) operators. Moreover, unloading coal on barges by Ship Unloader (SU) operators took a longer time than the specified estimated time. Therefore, this study aims to investigate whether the physical workloads of CHCR and SU operators are heavy and cause fatigue, which eventually causes a number of problems that lead to company losses, or whether the cause of these problems is not in operator's physical workload. This study involved 16 CHCR and SU operators with 3 work shifts. Physical workload measurement is referred on operator's pulse and temperature. Pulse measurement is manually done to both working and resting operators. Meanwhile, body temperature measurement is done before, when, and after working by using digital thermometer. Cardiovascular Load (CVL) approach is used to check pulses, to find out whether the workload is considered as heavy or light, while body temperature is referred to indicators or normal temperature range. The results of pulse measurements were processed and analyzed using the Cardiovascular Load (CVL) approach. Then, body temperature measurement is carried out to the operator’s before work, during work, and after work using a thermometer. The results show that the physical workload of CHCR and SU operators are classified as light and do not potentially lead them to work fatigue. In other words, the source of company's problems is not from physical workloads of CHCR and SU operator but likely from other aspects. Keywords: body temperature, cardiovascular load, operator, physical workload, pulse rate